Analisis Pengaruh Persepsi Manfaat Dan Citra Merek Terhadap Keputusan Pembelian Melalui Persepsi Nilai Pelanggan Sebagai Intervening (Studi pada Pengguna E-Toll card Tahun 2015 di Kota Semarang) - Sekarini, Dita Monica; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to investigate the influence of perceived usefulness, brand image, perceived risk, and perceivedÂ customer value, on purchase decision variable at e-toll card user in Semarang city. This study uses perceived usefulness, brand image, and perceived risk as the independent variables and perceived customer value as the intervening variable, and purchase decision as the dependent variable. This study uses quantitative methodology with Structural Equation Method (SEM) and uses primer and secondary data, the data analysis by collecting questionnaire respondents and company data. There are 181 respondents in this research. The analysis showed that the two independent variables are perceived usefulness (0,241), brand image (0,438), and perceived risk (0,158) has a positive and significant relationship to the intervening variable that is the perceived customer value. There is one independent variable that has a negative correlation to the dependent variables is perceived risk (0,017). There are three variables that have a positive and significant relationship to the dependent variable (purchase decisions) that perceived usefulness, brand image and perceived customer value. Meanwhile, perceived risk has a negative relationship and does not significantly influence the purchasing decision as the dependent variable.